Impact of pre-slaughter management on the welfare of goats and sheep - Lima, Luanda Rêgo de (2013)
The development of sheep and goat farming in Northeast region of Brazil is not only a subsistence activity among family farmers, but also in recent decades it has emerged as an important sustainable activity, overcoming the precarious subsistence stage and giving prospects for Brazilian agribusiness consolidation. However, some challenges still need to be overcome in order for this creation is profitable, such as the management of all stages of the creation of these animals, especially with the pre-slaughter management, where the greatest number of losses due to the stress caused to the animal, which consequently affects the welfare and the production. Thus, this review will address these issues in more details and clarify the possible damages caused by improper management during the pre-slaughter.